تقويم مدى قوة برنامج تعليم اللغة العربية للجمهور الناطقين بغير العربية من وجهة نظر المتعلمين: الجامعة الإسلامية العالمية بماليزيا نموذجا = Evaluating the teaching of Arabic to adults non-speakers of arabic program from their perspectives: IIUM as a case study - Masoud, Mahadi; Jalil, Marsufah (Department of Arabic Language and Literature, IIUM, 2014)
إن عملية التعليم والتعلم عملية مستمرة، ومتطورة ما دامت الحياة التعليمية قائمة، وهي متطورة بتطور الحياة الاجتماعية، لذا نجد المهتمين بالتعليم يعكفون من وقت لآخر على دراسة المناهج، وما يرتبط بها من مواد تعليمية، وموارد بشرية وغيرها بغية تطويرها والرقي بها. وفي مجال تعليم اللغة بوصفها لغة ثانية، أو أجنبية فإن عملية تعليمها تحتاج إلى مراجعة، ودراسة سواء أكانت على مستوى طرق التعليم ووسائله، أو منهج التدريس وكتبه، أو هيئة التدريس والمسؤولين عنه، وزمن التعلم ومدته. ومن هنا وقع اختيار الباحثين على موضوع تقويم مدى قوة برنامج تعليم اللغة العربية للماليزيين الكبار وفعاليته. سعى هذا البحث من خلال المنهج الوصفي الاستقرائي التحليلي إلى الإجابة عن السؤال الرئيس: ما مدى فعالية برنامج التعليم للمتعلمين؟ وقد طرح الباحثان استبيانا على عينة من الدارسين قدرها 42 دارسا، وقد أفضت الدراسة إلى نتائج متعددة من أهمها: أن البرنامج فعّال، والأمور التي يراعيها هذا البرنامج من زمن التدريس، ومكانه، و هيئة التدريس، وعدد المتعلمين في الفصول الدراسية، والمواد التعليمية، وطرق التعليم ووسائله، ورسوم التعليم تشبع حاجات المتعلمين، وميولهم، ويقبلون على الدراسة بانشراح غير أن الباحثين يوصيان بإعادة النظر إلى بعض النواحي المتعلقة بطرق التعليم، واستخدام وسائله من أجل تطوير البرنامج. Learning and teaching are continuous and progressive processes as long as there is education in life. It developed in tandem with the social life; therefore, educationists keep on reviewing periodically the syllabus and what relates to the teaching materials, the human resources and other relevant aspects for improvement and development. In the field of teaching Arabic as a second or foreign language, its process needs reviewing and studying either on the level of its teaching methods, syllabus, textbooks, the teaching staff, the policy makers and the period of teaching or learning. The researchers of this paper chose to study the effectiveness of the program of teaching Arabic to adults. Through descriptive, deductive and analytical methods, this paper attempts to answer the primary question: What is the effectiveness of teaching Arabic to adults. A set of questionnaire was distributed and 42 respondents returned the survey. Among the most important conclusions: that the program was effective. Matters related to the program such as class time and period, venue, teaching staff, number of teachers, teaching materials, fees and teaching methods seem to satisfy the students and their interest. The researchers recommend that there were rooms for improvement especially what relates to teaching methods in order to improve the program.